Pengembangan Ekonomi Kreatif Berbasis Seni Dan Budaya Dalam Menumbuhkan Eksistensi Desa Wisata Dikabupaten Kendal - Hamid Hanafi Hanan; Arkan Zahri; Afti Hilya Maulida; Qurrotul Aini; Salsabila Anis Widya; Zuanita Adriyani (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of creative economy based on art and culture in this modern era has a strategic role in strengthening the existence of tourist villages in Kendal Regency. This research was conducted in Kampung Ragam Warna in Kampung Mranggen, Kutoharjo Village, Kaliwungu District, Kendal Regency, where with poor environmental conditions economically and socially, these deficiencies can be transformed into a potential for sustainable tourist villages. This study analyzes the potential of local art and culture as the main attraction in the development of tourist villages. Through a qualitative approach, this study identifies various forms of art and culture that can be developed and the challenges faced in the process. The results of the study indicate that strengthening the creative economy based on art and culture not only increases the competitiveness of tourist villages, but also encourages the active participation of local communities in preserving cultural heritage. Empowerment of local communities and collaboration between the government, creative industry players, and the community are the main keys to creating sustainable tourist villages. In conclusion, an integrated and sustainable development strategy can increase tourist attractions and strengthen the position of Kendal Regency as a superior cultural tourism destination.